Assessing Foods and Services of Noah’s Favorites Food Hub in Richmond Village, Meycauayan, Bulacan: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Survey questionnaires were administered to regular and newbie customers of Noah's Favorites Food Hub to determine each point of view and feedback regarding the business research and other factors affiliated with it. Indeed, it solely focuses on assessing foods and services regarding taste, affordability, serving size, preparation time, and presentation. Regular customers were male, 26-35 years old, self-employed, 1-3 visits. The newbie customers were male, 15-25 years old, employed, and 1-3 visits. Regular and newbie customers assessed the foods and services as "completely agree" in terms of the variables above. There is a significant difference between the assessment of the two groups of customers. The customers encounter several problems. There are proposed recommendations. Noah's Favorites Food Hub introduced premium food bundles to customers to lower the original price by offering discounts and promos. Next, create a handbook that contains standard procedures for its product offerings to continue and maintain the quality of products and services to attract and engage prospective customers. Next, improve the work performance of Noah's Favorites Food Hub to establish consistency with its customers. Next, add a variety of products in the long run and provide a roof for each stall to secure the well-being of its customers. Lastly, apply, implement, and execute the essential recommendations given by this study's researchers.
Keywords: Food Hub; Assessment; Customers